Contemporary approaches to reducing scale formation in heat-exchange equipment - V. A. Golovin; S. A. Tyurina; V. A. Shchelkov (Российский технологический журнал)
Objectives. Scale formation and corrosion are serious problems for heat and power equipment. These processes, when intense, can completely block the operation of the system, accelerating corrosion and leading to clogging, local overheating, and burnouts and ruptures of boilers and pipes, which in turn can lead to major environmental problems. Therefore, protecting surfaces from scale formation and corrosion is an important task. Promising methods for preventing the development of undesirable consequences include changing the composition of polymer coatings, e.g., by introducing microencapsulated corrosion inhibitors, as well as surface modification approaches, such as hydrophobization of the polymer coating surface. The purpose of the present work is to analyze methods for reducing scale formation and the rate of corrosion processes, as well as to study the efficiency of modification of paints and coatings by introducing microencapsulated corrosion inhibitors.Methods. The study was based on the use of accelerated corrosion tests.Results. Existing methods for reducing scale formation and corrosion rate on the surfaces of heat and power equipment were analyzed. The efficiency of modifying protective polymer materials by introducing microcapsules containing an active phosphonate additive was compared with approaches involving the surface modification of such protective materials.Conclusions. It was determined that the modification of paints and coatings by introducing microencapsulated active additives can significantly reduce the rates of both scale formation and corrosion. By implementing stateof-the-art methods for modifying polymer coatings, a new generation of agents for efficiently preventing scale formation and corrosion processes can be developed for maintaining the high performance of heat-exchange equipment.